Analysis of the Tax Treatment of Inheritance Based on Laws Number 36 of 2008 - Najwah Fadhilah; Galuh Tresna Murti; Najwa Salsabila Az-Zahra; Rahayu Dwi Suryaningrum (Universitas Muhammadiyah Makassar, 2023)
Tax payment is a form of obligation for citizens. Income Tax Article 21 is one part of the applicable tax in Indonesia. The purpose of this study is to examine the tax treatment of inheritance calculations and compliance with the law based on Law No. 36 of 2008 concerning income tax. In this study using a qualitative approach method with bibliographical techniques. Based on the research results, it can be concluded that inherited assets are assets that are not subject to income tax (PPh) and inheritance can be categorized into 2 categories, namely tax subjects and non-tax objects. Inheritance is included as a tax subject if the inheritance has not been divided, while Inheritance in the tax object is the opposite of the tax subject. However, it can be categorized as a non-tax object if the heir has reported the Annual Income Tax Return (SPT PPh).